Simulação numérica do processo de deposição de parafina em cavidade cilíndricas contendo óleo parafínico estagnado - Krepcki, André Maurício Likes (2016)
The paraffin deposition in subsea pipelines is one of the main problems affecting the production and the oil suction operation, due to heat exchange between the oil pipe and seawater. With decreasing temperature over time, the solution begins to present small wax crystals, which deposits on the wall of the pipe obstructing the fluid flow and consequently reducing its diameter, resulting in an increase of power and operating costs oil companies. This study aims to analyze the temperature distribution a paraffinic oil considering a condition where there is a production line stopped. The analyzed geometry is cylindrical in shape and considered all the constant thermophysical properties and length unit. To obtain the results, carried out a numerical analysis using the finite volume method. For the validation of codes the results were compared to studies in the literature. The work is of great importance because it is within the line of Deposition Models Evaluation research Paraffin, aimed at reducing the costs involved in its removal.